Case Report: Rupture of the cardiac free wall after myocardial infarction confirmed by aortic computed tomography angiography - Liu, Jie; Chen, Weiqing; Li, Zihan; Liu, Nan; Mao, Cuiying (Frontiers in Cardiovascular Medicine, 2025)
IntroductionFree wall rupture is a rare complication of myocardial infarction, occurring as early as a few hours after myocardial infarction. It usually happens after transmural myocardial infarction and has a very high mortality rate. The diagnosis of free wall rupture requires echocardiographic evidence of pericardial leakage or pericardial tamponade. The patient's cause of death is often attributed to other causes such as cardiac arrhythmia unless determined by open heart surgery or autopsy. Diagnostic tools for post-infarction cardiac free wall rupture are limited to date.Case presentationWe present a case of myocardial infarction in a patient who presented with atypical chest pain. Subsequent coronary angiography revealed small vessel disease, however, the patient's severe clinical presentation was not consistent with small vessel disease. The initial clinical presentation did not rule out aortic dissection, prompting further investigation through aortic computed tomography. This imaging technique revealed a rupture of the free wall of the heart accompanied by a large amount of bloody pericardial effusion. Unfortunately, attempts to puncture and drain the effusion were unsuccessful and the patient eventually succumbed.ConclusionsWhen patients present with more severe clinical manifestations that are not consistent with myocardial infarction, it is important to be alert to the possibility of cardiac rupture in addition to identifying the possibility of aortic dissection. Aortic CTA may be able to confirm the diagnosis of cardiac rupture.